(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, in accordance with the decree of the Fergana regional administration No. 421 of 1898 "On the opening of public libraries and classrooms in regional and city centers", public libraries have been created in the cities of Osh, New Margilan, Kokand, Namangan. Andijan, Skobelev,where their activities and books collection were desribed. In preparing the article, the documents of the National Archives of Uzbekistan were used, Fund I-1, opis-13, collection-102 and Fund I-19, opis-1, collection-1167